Optimal home and hospital laundering of reusable surgical scrubs: Systematic literature review - Je'nine Horn-Lodewyk; Tanya Wainwright; K-Cee Lessing; Daniel Otto; Jani H. Fourie (AOSIS, 2023)
Background: Theatre personnel can spread healthcare-associated infections through contaminated surgical scrubs. Decontamination of surgical scrubs through optimal methods is important to minimise transmission of microorganisms from theatre personnel's clothing to different areas in the hospital and their homes. Aim: This study aimed to review the literature on the optimal home and hospital laundering methods for the decontamination of reusable surgical scrubs worn by theatre personnel. Method: A systematic literature review of previous studies on laundering reusable surgical scrubs was performed. A review question was formulated using the patient, intervention, comparison and outcome (PICO) framework. A literature search was performed using ScienceDirect, Web of Science, ProQuest, EBSCOhost and Google Scholar. Results: A direct link could be established between the cycle length and water temperature. The higher the water temperature, the shorter the washing cycle required. After a load has been washed in low or medium water temperatures, tumble drying and ironing should follow. Despite the water temperature, a disinfectant must be added to the load. Conclusion: Health professionals and hospital management should be aware of optimal laundering guidelines for hospital and home laundering as part of infection control. Water temperature, time, mechanical action, type of disinfectant and heat are factors influencing the successful removal of bacteria and other pathogens and represent the baseline of this article. Contribution: Home-laundering of reusable surgical scrubs should follow strict guidelines. When these specific guidelines are applied, the effects of home-laundered scrubs will not negatively impact either the theatre or the home environment.